2022
DOI: 10.1037/gdn0000158
|View full text |Cite
|
Sign up to set email alerts
|

Personality and group psychotherapy outcome: The lack of influence of traits from the five-factor model.

Abstract: Although there is accumulating evidence of the importance of personality in predicting group psychotherapy outcomes, the extent to which Big Five personality traits predict group psychotherapy outcomes is debatable. Thus far, findings from individual treatment studies suggest Big Five traits have a marginal-to-small impact on the success of psychotherapy. Yet, results from the handful of group therapy studies on Big Five traits are equivocal. Moreover, extant research on Big Five traits and group treatment out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Results lend support for the PSDM in a clinical context and underscore the importance of perfectionism’s influence on social disconnection that should be taken into account when treating patients with perfectionism (also see Shahar et al, 2004). Importantly, in subsequent analyses, Smith, Hewitt, et al, 2021 found that, unlike perfectionism, Big Five personality traits did not predict greater or lower symptom change. This lends support to the specificity of Hewitt et al’s (2020) finding and underscores that perfectionism is not only relevant to the experience of depression but also can impede treatment benefit.…”
Section: Impact Of Perfectionism On Psychotherapy and Therapeutic All...mentioning
confidence: 77%
See 2 more Smart Citations
“…Results lend support for the PSDM in a clinical context and underscore the importance of perfectionism’s influence on social disconnection that should be taken into account when treating patients with perfectionism (also see Shahar et al, 2004). Importantly, in subsequent analyses, Smith, Hewitt, et al, 2021 found that, unlike perfectionism, Big Five personality traits did not predict greater or lower symptom change. This lends support to the specificity of Hewitt et al’s (2020) finding and underscores that perfectionism is not only relevant to the experience of depression but also can impede treatment benefit.…”
Section: Impact Of Perfectionism On Psychotherapy and Therapeutic All...mentioning
confidence: 77%
“…This suggests socially prescribed perfectionism might function as a concomitant of depression, although, as indicated above, it does interact with stressors in predicting depressive symptoms. Moreover, we recently reported meta-analytic evidence derived from clinical and nonclinical studies that the relationship between socially prescribed perfectionism and depressive symptoms is unidirectional, with socially prescribed perfectionism predicting increased depression but not the reverse (Smith, Hewitt, et al, 2021). However, there is need to examine this issue further longitudinally as Vaillancourt and Haltigan (2018) suggested in the McMaster Teen Study that depression might predict socially prescribed perfectionism rather than vice versa.…”
Section: Evidence Of the Relevance Of Perfectionism To Depression Per...mentioning
confidence: 99%
See 1 more Smart Citation